Implications of Shariah by-Law on Moslem Dress Code on Women in Indonesia - Akhmad Najibul Khairi (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
Following the fall of the New Order regime in 1998, Indonesia commenced reformation to its government system from the authoritarian centralist system of Suharto’s New Order toward a democratic decentralized system. As a result, many local governments have used these new powers to locally introduce Sharia-based regulations known as Perda Shariah. However, pros and cons have emerged due to the enactment of such Shariah-based regulations. One of the controversial and discriminating point in the implementation of Sharia-based regulation is the regulation on Islamic dress code that requires Muslim women to wear veils. The report from National Commission on Violence Against Women (2010, p.III), for example, has identified around 21 policies concerning the Islamic dress code. For this reason, I will argue that Sharia-based regulations on Moslem dress code have negative impacts on women and minority groups. This essay will then be structured into two sections. The first is the explanation of the Sharia- based regulation on Moslem dress code. The second part is the analysis of the impact of these regulations on women.